2016
DOI: 10.1021/acsnano.6b03135
|View full text |Cite
|
Sign up to set email alerts
|

Internal Morphology-Controllable Self-Assembly in Poly(Ionic Liquid) Nanoparticles

Abstract: Precise control of the interior and outer shapes of polymer nanoparticles has found broad interest in nanosciences, for example, in fundamental studies of their physical properties, colloidal behavior, and corresponding applications. Realizing such control below the 50 nm scale (i.e., a size scale close to individual polymer chains) requires accurate manipulation of polymerization techniques and a judicious choice of the chemical structure in monomers and/or polymers. Here, we constructed a series of well-defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
61
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 66 publications
(61 citation statements)
references
References 45 publications
0
61
0
Order By: Relevance
“…While remarkable progress has been achieved in bulk BCP self‐assembly towards obtaining arbitrary features with smaller domain sizes, only recent studies have indicated that solution self‐assembly of BCPs can also produce several complex nanostructured nanoparticles with domain sizes in the sub‐50 nm range . In the process of internal phase separation of BCPs in colloidal 3D confinements, various morphologies can be obtained, e.g., Janus, lamellae, cylinder, or dot patterns . Beyond the vibrant field of supracolloidal assembly, such internally structured nanoparticles may find interesting applications at the monomeric level, for their bulk multicompartment‐based nature (e.g., as nanoreactors, nanocontainers for controlled release) as well as for their topographical or chemical surface heterogeneities, leading to their designation as patchy nanoparticles .…”
Section: Introductionmentioning
confidence: 99%
“…While remarkable progress has been achieved in bulk BCP self‐assembly towards obtaining arbitrary features with smaller domain sizes, only recent studies have indicated that solution self‐assembly of BCPs can also produce several complex nanostructured nanoparticles with domain sizes in the sub‐50 nm range . In the process of internal phase separation of BCPs in colloidal 3D confinements, various morphologies can be obtained, e.g., Janus, lamellae, cylinder, or dot patterns . Beyond the vibrant field of supracolloidal assembly, such internally structured nanoparticles may find interesting applications at the monomeric level, for their bulk multicompartment‐based nature (e.g., as nanoreactors, nanocontainers for controlled release) as well as for their topographical or chemical surface heterogeneities, leading to their designation as patchy nanoparticles .…”
Section: Introductionmentioning
confidence: 99%
“…[ 19 ] The original morphology and structure of biomaterials can be well preserved at cryogenic temperatures. Inspired by the successful utilization of cryo‐EM in biological sciences, researchers have extended its applications to investigate other beam and air‐sensitive materials, such as polymers [ 20 ] and nanomaterials. [ 21 ] Cryo‐EM not only inhibits the damage of sensitive materials from air and electron beams during sample transfer and characterization, but also preserves their intrinsic structures, which enables us to image them at the micro/nano/atomic scale.…”
Section: Introductionmentioning
confidence: 99%
“…Chemical absorption of CO2 by aqueous amine solutions is a conventional and well-developed post-combustion capture technology but suffers from corrosion, volatility, toxicity, degradability and high energy consumption for regeneration [10][11][12]. Alternatively, various highly porous adsorbents, which operate mainly via physical adsorption, have been studied over the past two decades for potential use in pressure/temperature swing Polytriazoliums have been previously seldom studied and have not been investigated in the form of PILs until very recently [44][45][46][47][48][49]. A triazolium unit has two isomers, that is, 1,2,3-, and 1,2,4-triazoliums, depending on the position of nitrogen atoms within the ring.…”
Section: Introductionmentioning
confidence: 99%
“…A triazolium unit has two isomers, that is, 1,2,3-, and 1,2,4-triazoliums, depending on the position of nitrogen atoms within the ring. Among them, 1,2,3-triazole derivatives that are precursors for 1,2,3-triazolium ILs can be easily obtained by copper catalyzed azide-alkyne cycloaddition [50,51] [47][48][49]61].…”
Section: Introductionmentioning
confidence: 99%